Factor yang Mempengaruhi Kesiapsiagaan Perawat Gawat Darurat dalam Manajemen Bencana: Literatur Review - Desi Holifatus Suaida; Ida Wahyuni; Tri Nili Sulayfiyah; Mery Eka Yaya Fujianti (Indonesian Health Science Journal, 2024)
Background: A disaster is an event that threatens human life. Disasters result in high death rates, injury rates, infrastructure damage and economic losses for communities. Support from the role of hospitals and health workers, especially nurses, is very much needed to reduce the number of victims in each disaster, especially in improving disaster preparedness. The preparedness stage includes planning the number of patients, evacuating patients to hospitals, preparing medical equipment, and preparing disaster training to carry out nursing actions. Purpose: This study aims to determine the factors that influence the preparedness of health center nurses and emergency room nurses in disaster management. Methods: We used document studies to search for journals used in the literature review. The journals used in the literature review were obtained through a database-based search for international journal scienced direct, PubMed. The researcher wrote the keywords, namely "disaster management", "emergency nursing", "disaster response", and selected full text. Results: Based on the 6 research literature, it was found that the factors that influenced preparedness included length of work, level of education, experience following disaster training, availability of facilities, and infrastructure. Conclusion: Nurses play an important role in the disaster management process, therefore, nurses should improve flood disaster preparedness management